Brian's winter - Paulsen, Gary (Brian's Saga, 1996)
Instead of being rescued from a plane crash, as in the author's book Hatchet, this story portrays what would have happened to Brian had he been forced to survive a winter in the wilderness with only his survival pack and hatchet.